Injection therapy for carpal tunnel syndrome: A systematic review and network meta-analysis of randomized controlled trials. - Fu-An Yang; Hsun-Yi Wang; Tien-Yu Kuo; Chih-Wei Peng; Tsan-Hon Liou; Reuben Escorpizo; Hung-Chou Chen (PLoS ONE)
Various injectants are available for the treatment of carpal tunnel syndrome. This systematic review and network meta-analysis was conducted to investigate the effectiveness of different injection therapies in alleviating the symptoms of carpal tunnel syndrome. Various databases were searched for relevant studies from inception until May 10, 2023. Eligible studies were identified using the patient (P), intervention (I), comparison (C), and outcomes (O) model, which involved (P) participants with carpal tunnel syndrome, (I) an intervention based on injection therapy, (C) the use of placebo or another injectant as a control treatment, and (O) the measurement of clinical and electrodiagnostic outcomes of interest. A total of 18 studies were included in the analysis. The network meta-analysis revealed that platelet-rich plasma is effective in the treatment of carpal tunnel syndrome in terms of symptom and pain relief and functional improvement in both the short and long term, whereas steroids are effective only in the short term. Additionally, injections of dextrose solution may offer long-term pain relief as well as short- and long-term symptom alleviation and functional improvement. The study findings suggest that platelet-rich plasma should be used as the first-line treatment for carpal tunnel syndrome, with dextrose and steroids serving as alternative treatment options.